2018
DOI: 10.1038/s41430-018-0313-9
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide adherence to Mediterranean Diet between 1960 and 2011

Abstract: Word count: 6944. Number of figures: 2. Number of tables: 3. Number and names of supplementary online material if applicable: no. 2 Background: From the 1960s to the early 21st-century adherence to the Mediterranean diet (MD) declined around the world. This was partly due to the westernization of eating habits. However, in the last decade a new variable came into play, the economic crisis, which may have affected dietary patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
107
2
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(130 citation statements)
references
References 42 publications
8
107
2
5
Order By: Relevance
“…These countries (except NMK, no information available) were ranked from best to worst MAI as follows: GR > IT > SP > PT > BG > CY. They were also reported to have reduced their MAI scores in the last decades, indicating a shift away from the traditional MD pattern [ 34 ]. Further, the sample population from SP, which exhibited the highest adherence to the MD, reached an average MEDAS of 8.35 ± 1.65 and was very close to the value attained in the PREDIMED validation study (8.68 ± 1.90) [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…These countries (except NMK, no information available) were ranked from best to worst MAI as follows: GR > IT > SP > PT > BG > CY. They were also reported to have reduced their MAI scores in the last decades, indicating a shift away from the traditional MD pattern [ 34 ]. Further, the sample population from SP, which exhibited the highest adherence to the MD, reached an average MEDAS of 8.35 ± 1.65 and was very close to the value attained in the PREDIMED validation study (8.68 ± 1.90) [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, MedDiet is a settled cultural heritage of the Portuguese population, with ancestral influence from the Mediterranean neighbors (26). Several studies have shown that Mediterranean basin populations tended to abandon the traditional diet during the last decades (27,28)and the same occurred in Portugal (26). The major concern is the early abandonment of Med-Diet during childhood, adolescence and youth, leading to the replacement of traditional dietary habits with an increasing consumption of red meat, butter, animal fats, added sugars and salty foods (29)(30)(31)(32), which increased the risk of obesity and several health problems (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…No entanto, a DM é um património cultural adotado pela população portuguesa, com influência ancestral dos vizinhos do Mediterrâneo (25). Vários estudos mostraram que as populações do Mediterrâneo tenderam a abandonar a dieta tradicional nas últimas décadas (26,27) e o mesmo ocorreu em Portugal (25). A principal preocupação é o abandono precoce da DM durante a infância, adolescência e juventude, levando à substituição de hábitos alimentares tradicionais por um consumo crescente de carne vermelha, manteiga, gorduras animais, açúcares adicionados e alimentos salgados (28)(29)(30)(31), o que aumenta o risco de obesidade e vários problemas de saúde (32)(33)(34).…”
Section: Discussionunclassified
“…Likewise, it has been suggested that there might be stronger selection pressure on the FADS1/FASD2 block in southern Europeans [95]. In Spain, the adherence to the Mediterranean diet pattern [99] is still relatively high in older subjects, but is decreasing in young people [100,101]. Although some studies specifically carried out in the Spanish Mediterranean population, have analyzed the association between several FADS and ELOVL candidate gene polymorphisms and PUFA concentrations [102][103][104][105][106], no study has investigated such associations at the GWAS level.…”
Section: Introductionmentioning
confidence: 99%